2017
DOI: 10.4172/2472-1921.100058
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload Effect on Serum Levels of Glucose, Insulin and HOMA-IR was Ifluenced by the Type of Fat in Female Sprague-Dawley Rats Fed High-Fat-Diets

Abstract: Objective: This study was conducted to examine the effect of iron supplementation on serum levels of glucose, insulin and HOMA-IR, and to examine the histological iron deposition in tissue in female Sprague-Dawley rats fed high-fat-diets (HFDs). Methods:Rats were divided into three main groups: normal fat diet (NFD), high saturated fat diet (HSFD) and high monounsaturated fat diet (HMUSFD). After 6 weeks, rats were sub-divided into three sub-groups for intraperitonial injection of iron (control group, dose1 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The increased glucose level after irradiation might be related to endocrine glands function abnormalities induced by irradiation that promote the secretion of biologically active peptide which has related to carbohydrate metabolism by increasing gluconeogenesis in liver (28) . In the same line, excess iron alters glucose homeostasis and causes a significant increase in glucose level (29) through increasing oxidative/ nitrative stress and reducing antioxidant capacity. Also, the increase in glucose level may be due to the alterations in the hepatic gluconeogenesis enzymes and lipid synthesis as a result of oxidative stress and mitochondrial dysfunction (30) .…”
Section: Discussionmentioning
confidence: 99%
“…The increased glucose level after irradiation might be related to endocrine glands function abnormalities induced by irradiation that promote the secretion of biologically active peptide which has related to carbohydrate metabolism by increasing gluconeogenesis in liver (28) . In the same line, excess iron alters glucose homeostasis and causes a significant increase in glucose level (29) through increasing oxidative/ nitrative stress and reducing antioxidant capacity. Also, the increase in glucose level may be due to the alterations in the hepatic gluconeogenesis enzymes and lipid synthesis as a result of oxidative stress and mitochondrial dysfunction (30) .…”
Section: Discussionmentioning
confidence: 99%
“…The ways in which these interact are numerous and not fully understood. A study in rat models showed that iron overload affected serum levels of glucose, insulin and insulin resistance differently, depending on the level of fatty acid saturation of the diet [ 17 ]. Rat studies have also shown interaction between iron levels and desaturases, where high iron levels are associated with both lower delta-5 desaturase (D5D) activity and delta-6 desaturase (D6D) (inserting double bonds after the 5th resp.…”
Section: Introductionmentioning
confidence: 99%